Book clubs as strategy for increasing nutrition knowledge among general population: Pilot study - López-Díaz, María Teresa; Romero, Irene; Martín, María Ángeles; Sánchez-Ballesta, María Teresa; Gómez-Estaca, Joaquín; Álvarez-Cilleros, David; Ramos, Sonia; Mesias, Marta; Peñas, Elena; Pérez-Jiménez, Jara (Revista Española de Comunicación en Salud, 2023)
Introduction: The spread of false news related to nutrition shows the need to provide general public validated information on food and health, inducing them to follow healthy dietary habits. Objective: To assess whether attendance to book clubs devoted to scientific disseminations books is a useful strategy for improving nutritional knowledge among the population. Methodology: 65 adults participated in a reading club, attending a research center once a month for 4 months to talk about informative scientific books on food/nutrition. The knowledge of the participants was monitored through a survey performed in all the sessions of the club. Results: Participants were mostly female with university studies. Attendance to the book clubs caused a significant increase (P < 0.05) in the number of correct answers on a questionnaire about common misbeliefs on the topics covered in the discussed books. Participants showed a high degree of satisfaction with the activity and willingness to read more scientific dissemination books, even when most of them were not previously usual readers. Conclusions: Book clubs based on popular science books and led by scientists with expertise in the field could increase nutritional knowledge among general population, which should be further explored in different socioeconomic contexts.
Keywords: nutrition misbeliefs; food myths; scientific dissemination; food literacy; nutritional education